Gender and Text: How Societal Awareness of Gender and Identity Diversity Changes the Production of Texts – Illustrated with the Example of German - Scheller-Boltz, Dennis (2023)
Societies that need to deal with diversity also need to deal with the ways in which their members use texts, conventions for different text types and, consequently, with the production of texts itself. As societies change and become more diverse, texts will have to reflect this change eventually. Yet, how exactly does this social diversity affect our minds? How does the awareness of diversity influence our texts and their production? In this article, I will examine – primarily on the basis of general observations in the press and the media – the current developments in changes in German society. I will discuss social diversity and illustrate the different ways in which these factors influence speakers of German when they produce texts. By using examples from three categories of texts – oral texts, forms of address, job advertisements – I will show changes in text types and their conventions. The result of this study will be that a mix of different denominations or labels can increase the number of people reached, that language can perform substantially more functions and be substantially less discriminatory than is usually assumed, and that at the end of the day, generic masculine forms almost always address male persons exclusively. We will see that text types and their conventions are subject to change, and that this change is still evolving. Where this evolution of text types and their conventions will lead, remains to be seen.
Keywords: gender; gender linguistics; text conventions; text production; masculine generics; gender-fair language; language policies